A Power Comparison Of Robust Test Statistics Based On Adaptive Estimators. - Keselman, H. J.; Wilcox, Rand R.; Algina, James; Fradette, Katherine; Othman, Prof.Madya Abdul Rahman (2004)
Seven test statistics known to be robust to the combined effects of nonnormality and variance heterogeneity were compared for their sensitivity to detect treatment effects in a one-way completely randomized design containing four groups.